PERHITUNGAN BEBAN PANAS PADA PALKA KAPAL PURSE SEINE KM. DUTA MULIA DI PEKALONGAN - Vita Rumanti K.; Budhi Hascaryo Iskandar (Buletin PSP, 2006)
The Indonesian fishermen usually use ice and salt as refrigerants to keep of catch before it is landed. The amount of refrigerants bringing in a trip usually only based on the prior experienced of senior fishermen without any exact estimation.This paper tries to analyze the amout of ice in a trip of a fishing vessel (KM. Duta Mulia) in Pekalongan by calculating heat receiving in fish holds. By this approximation, the minimum amout of ice that needed in a trip can be obtained. the fishermen usually bring 20.000 kg ice in a trip (40 day).One of the result shows the minimu amout of ice that needed for refrigerating 17.460 kg catch within 40 day is 13.180.692 kg. Based of this result, the fisherman might reduce the amout of ice that they usually bring in a trip.Keywords: fish hold capacity, insulations, and heat load